VARIABILITAS DAN KEMAJUAN GENETIK KARAKTER AGRONOMIS GALUR-GALUR F2:4 HASIL PERSILANGAN FORE BELU DAN LOKAL SABU - Mau, Yosep Seran; Neno, Abner; Ndiwa, Antonius S.S.; Oematan, S.S. (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
Mungbean is the third most important legume crop in Indonesia, and in East Nusa Tenggara Province in particular, as the crop is an important source of protein and vitamins, and also well adapted to dry land conditions of the province. However, the mungbean productivity in the farmer level is low, partly because of the use of low yielding local varieties. Mungbean productivity can be increased through the production of superior varieties, which can be done through artificial crossing using local germplasm. Crossbreeding between NTT local varieties has been carried out, between Fore Belu and Lokasl Sabu. This research aims to determine the variability of agronomic characters and the genetic advance of F2:4 lines resulting from Fore Belu and Lokal Sabu crosses. The research was carried out in the field involving 30 F2:4 lines and two parental varieties, each consisting of two replications. The variables observed included flowering date, harvesting date, plant height, number of pod cluster, number of pods, and seed weight per plant. Harvesting date had a narrow genetic and phenotypic variabilities while the other evaluated characters had wide/high variabilities. Heritability of all observed characters were classified high. Genetic advance of agronomic characters, especially the number of pods per plant, the number of productive branch per plant and the weight of seeds per plant were categorized as high. The F2:4 lines that showed desirable agronomic characters included G1, G7, G9, G21, G26, G27, G28, G29, G30, G32, G34, G35 and G39. These lines were selected for further testing in the F5 generation.